Harmful Introductions and Ballast Water Management- an Emerging Problem in the Northern Adriatic - Jakomin, Livij; David, Matej (Promet - Traffic&Transportation, 2002)
The article calls our attention to the existing dangers of potentiallyharmful 01ganisms being introduced in our sea withships ballast water and to the need of having this maller undercontrol. To this end the article presents the importance of ballastwater for a ship, organisms in ballast water, some cases ofharmful introductions and the case of Slovenia. Furthermore,legal aspects, ballast water management methods/techniquesand monitoring aspects are presented. Finally, the article dealswith perspectives for the regulation of the ballast water issue.